REGISTRATION OF INTERNAL MORPHOLOGICAL CHARACTERISTICS OF THE TOOTH USING DENTAL PHOTOGRAPHY - Todor T. Uzunov; Dimitar Kosturkov; Tsonko Uzunov; Dimitar Filchev; Boiko Bonev; Andon Filchev (Peytchinski Publishing, 2015)
Purpose: Dental photography plays important role in the transfer of information between dentists as well as in communication between them and the dental technicians. It is very important to take precise photos of external and internal morphological characteristics of the teeth. There are different methods for that. The aim is to establish a protocol for registration of internal morphological characteristics of teeth by digital dental photography. Material and methods: For the accomplishment of the aim60intact frontal teeth of 30 patients aged between 18 and 20 years were photographed. The following basic and additional devices for dental photography were used: 1. Digital SLR (DSLR): • Body - Nikon D90 • Lens - Nikon AF-S Micro Nikkor 105 f / 2.8G VR • Flash - Nikon SB-R-200 Speedlight remote kit R1 2. Lingual contraster 3. Reflective disk with silver surface Lingual contraster was placed behind the respective tooth when taking photos. Light reflector was placed sideways near patient's head. The head of the flash that is near to the reflector was oriented towards it. The other flash on the opposite side, activated at a minimum power, was directed to the tooth row. Results: Internal characteristics of the tooth - enamel cracks, translucency, transparency, opacity and opalescence were easily and predictably recorded by the described methodology. Conclusions: The method suggested by us can be successfully used for recording the internal morphological characteristics of the tooth.